2020
DOI: 10.1001/jamanetworkopen.2020.25850
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Vitamin D3 Supplements on Development of Advanced Cancer

Abstract: IMPORTANCEEpidemiologic and trial data suggest that vitamin D supplementation may reduce metastatic cancer and cancer mortality, reflecting shared biological pathways. OBJECTIVE To follow up on the possible reduction in cancer death in the Vitamin D and Omega-3 Trial (VITAL) with an evaluation of whether vitamin D reduces the incidence of advanced (metastatic or fatal) cancer and an examination possible effect modification by body mass index. DESIGN, SETTING, AND PARTICIPANTS VITAL is a randomized, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(104 citation statements)
references
References 34 publications
2
102
0
Order By: Relevance
“…However, cancer mortality was reduced by 13% (95% CI, 4% to 21%) in the five available trials (1591 deaths). In another secondary analysis, there was a significant reduction in advanced cancers (metastatic or fatal) for those randomized to vitamin D compared with placebo [ 97 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…However, cancer mortality was reduced by 13% (95% CI, 4% to 21%) in the five available trials (1591 deaths). In another secondary analysis, there was a significant reduction in advanced cancers (metastatic or fatal) for those randomized to vitamin D compared with placebo [ 97 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Authors argued that the reason for this difference could be the decreased bioactivity of vitamin D in overweight or obese people, as well as the fact that using the same dose of vitamin D 3 would result in a greater volumetric dilution and, consequently, a minor variation of active vitamin D levels. Unfortunately, case numbers for mortality due to breast cancer were too small to be interpreted [ 119 ]. This argument was supported by other authors like Grant et al, who defended the importance of designing protocols and analyses including serum 25(OH)D 3 concentrations as the main analysis parameter rather than using the intake dose of vitamin D 3 [ 120 ].…”
Section: Antioxidants and Breast Cancermentioning
confidence: 99%
“…Subsequent analysis found evidence for a protective effect; a second analysis of the data suggested decreased cancer mortality in some subgroups of enrolled individuals receiving vitamin D ( 18 , 120 ). Very recently, a further analysis of the VITAL data suggests that vitamin D reduces the risk of metastatic or fatal cancer ( 121 ). Apparently consistent with this idea, a meta-analysis of 10 clinical trials (81362 pooled participants) found vitamin D supplementation was associated with a significantly lower risk of cancer mortality ( 47 ).…”
Section: Cancermentioning
confidence: 99%